2007
DOI: 10.1017/s095252380707037x
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 35/36 is phosphorylated at regulatory sites in the retina

Abstract: Connexin 35/36 is the most widespread neuronal gap junction protein in the retina and central nervous system. Electrical and/or tracer coupling in a number of neuronal circuits that express this connexin are regulated by light adaptation. In many cases the regulation of coupling depends on signaling pathways that activate protein kinases such as PKA, and Cx35 has been shown to be regulated by PKA phosphorylation in cell culture systems. To examine whether phosphorylation might regulate Cx35/36 in the retina we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 62 publications
4
95
0
Order By: Relevance
“…Further studies showed that in vivo these gap junctions typically comprise small numbers of connexons (341,345) made only of Cx36 in vivo (65,421,478,479,538) within the islets of adult, control animals of all species investigated so far, whereas under certain in vitro conditions they may also contain Cx43 (91,296,309). Cx36 is a 321-amino acid protein with a long (99 amino acid) cytoplasmic loop containing an unusual stretch of 10 glycine residues (94) and a short cytoplasmic COOH-terminal region containing potential recognition sites for casein kinases I and II, cAMP-dependent protein kinase, and calmodulin-dependent protein kinase II (60), consistent with the finding that, at least under certain conditions, the function of Cx36 may be regulated by phosphorylation (3,274,550). Cx36 does not form functional cell-to-cell channels with other connexins (201), and the homotypic channels it makes differ from those made by other connexins by a small unitary conductance (10 -15 pS) and minimal voltage sensitivity (201,360,512).…”
Section: B the Connexin And Coupling Patternsupporting
confidence: 73%
“…Further studies showed that in vivo these gap junctions typically comprise small numbers of connexons (341,345) made only of Cx36 in vivo (65,421,478,479,538) within the islets of adult, control animals of all species investigated so far, whereas under certain in vitro conditions they may also contain Cx43 (91,296,309). Cx36 is a 321-amino acid protein with a long (99 amino acid) cytoplasmic loop containing an unusual stretch of 10 glycine residues (94) and a short cytoplasmic COOH-terminal region containing potential recognition sites for casein kinases I and II, cAMP-dependent protein kinase, and calmodulin-dependent protein kinase II (60), consistent with the finding that, at least under certain conditions, the function of Cx36 may be regulated by phosphorylation (3,274,550). Cx36 does not form functional cell-to-cell channels with other connexins (201), and the homotypic channels it makes differ from those made by other connexins by a small unitary conductance (10 -15 pS) and minimal voltage sensitivity (201,360,512).…”
Section: B the Connexin And Coupling Patternsupporting
confidence: 73%
“…D1 dopamine receptor activation in mouse AII amacrine cells leads to a PKA-mediated phosphorylation of Cx36 correlating with a decrease of dye coupling in vivo (Urschel et al 2006). In the teleost retina, it was shown using phospho-specific antibodies that the natural stimulus of dark-adaptation dramatically increased the levels of Cx35 (the teleost ortholog of Cx36) phosphorylation (Kothmann et al 2007). Furthermore, these phosphorylation events occurred at sites shown to regulate Cx35 channel gating using in vitro expression studies (O'Brien et al 2004).…”
Section: Rapid Regulationmentioning
confidence: 99%
“…Because no changes in membrane Cx36 content or organization occurred over these time scales, this suggests that channel gating by phosphorylation is a potential regulatory mechanism. In rat epithelial cells, PKC phosphorylation of Cx43 regulates channel conductance (35) and PKC␦ has been shown to directly phosphorylate Cx43 in fibroblasts (51), where the Cx36 C terminus contains similar serine residues that may be phosphorylated by PKC␦ (52). Protein kinase A also regulates Cx36 in the retina through phosphorylation (34) and in the islet PKA has been shown to regulate GLP1-regulated synchronized [Ca 2ϩ ] i dynamics (53).…”
Section: Low Levels Of Pro-inflammatory Cytokines Disrupt [Ca 2ϩ ] I mentioning
confidence: 99%